North American missionaries developed a North American-style school to prepare their children for life back in North America. Issue 4 (October 2019) - Buschman, Lawrent L.
In her article "Sacred children and colonial subsidies" Anicka Fast suggests that the missionaries of the American Mennonite Brethren Mission developed a school for their children in order to separate the missionary children from the Congolese children. That is an unfortunate misinterpretation of the historical situation. The missionary children were always intimately associated with Congolese children on the mission stations. The missionary children's school was developed to train the missionary children so they could return to North America, where they were legally expected to return and live. They were not immigrants in the Congo. They needed a "North American-style education" so they would have a reasonable chance of success when they returned to North America. The school itself eventually was moved to Kinshasa where it developed into the American School of Kinshasa, which serves a wide spectrum of black and white children from around the world. The matter of colonial subsidies was only tangentially related to the development of the school.